Aspergillus fumigatus meningitis in an immunocompetent young woman - Balram Rathish; Arun Wilson; Anup Warrier; Roshni Pillay; Joe Thomas (Wolters Kluwer Medknow Publications, 2020)
Aspergillus meningitis is a rare clinical entity that is much more frequently observed among immunocompetent patients. Here we present the case of a 28 year old immunocompetent lady with Aspergillus fumigatus meningitis possibly following spinal anaesthesia for her caesarean section. The diagnosis of Aspergillus meningitis is very difficult and challenging. Even after diagnosis, clinical outcomes remain poor with treatment. We wish to highlight the need for high index of suspicion for Fungal meningitis in patients presenting with meningism after Neurosurgeries and procedures involving invasion into the CSF compartment.